International Legal Status of the Arctic - KUZNETCOV, Aleksandr Vasilyevich (Journal of Environmental Management and Tourism, 2016)
The research explores the legal status of the Arctic. The article presents an analysis of legislations of different countries that have claimed Arctic territories and territories of the continental shelf as theirs (Russia, Canada, USA, Denmark, and Norway). The article also analyses international agreements aimed at settlement of the disputes over the Arctic. The interest in the Arctic appeared only in the twentieth century. That interest primarily relates to the large amounts of resources in the depths of the Arctic. Thus, the issue of legally-based ownership of the Arctic territories and their belonging to any country is a contemporary issue.
Keywords: The Arctic; continental shelf; international legal status; national legislation; international agreements; sector theory; disputes